Artificial Intelligence in Education: Ethical Challenges and Policy Implications for Inclusive Learning - Afkarul Azmi; Samsul Arifin; Yola Mutia Damayanti; Fadli Agus Triansyah; Ismaul Fitroh (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
The growing reliance on intelligent computational systems in education has redefined pedagogical practices, governance structures, and learner experiences, particularly within inclusive learning environments. This study examines ethical challenges and policy implications associated with these systems by employing a qualitative normative approach grounded in critical literature analysis and conceptual synthesis. Drawing on peer-reviewed studies addressing inclusion, ethics, and educational governance, the analysis explores how design principles, institutional policies, and leadership practices influence equitable learning outcomes. The findings reveal that inclusive education is enhanced when ethical considerations such as fairness, transparency, accessibility, and data protection are systematically integrated into policy and institutional decision-making. Conversely, insufficient governance and ethical oversight risk reinforcing structural inequalities and marginalizing vulnerable learner groups. The study highlights that inclusive outcomes depend on the balance between technological mediation and human-centered pedagogy, supported by coherent policy frameworks and professional capacity building. This research contributes to contemporary educational discourse by articulating the necessity of aligning ethical responsibility with policy development to ensure that educational innovation advances equity, participation, and social justice within diverse learning contexts.